CORRELATION BETWEEN FINGER VENULE POSITION AND ASTHMA SEVERITY IN CHILDREN AGED 3 YEARS OR YOUNGER AT LE VAN THINH HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Bronchial asthma is a common chronic inflammatory disease of the respiratory tract that affects millions of people worldwide, particularly children. The index finger is a specialized diagnostic method used to identify diseases in children under 3 years of age. This study aims to investigate the relationship between the length of the index finger and the severity of bronchial asthma in patients aged ≤ 3 years at Le Van Thinh Hospital.Subjects and Methods: This is a cross-sectional analytical study conducted on 100 pediatric patients diagnosed with bronchial asthma, aged ≤ 3 years, who were treated at the Department of Pediatrics (inpatient and outpatient) of Le Van Thinh Hospital, Thu Duc City, from January 2025 to April 2025.Results: Distribution of chi văn locations: Phong quan (57.00%), Khi quan (35.00%), Menh quan (8.00%). Distribution of asthma severity: mild bronchial asthma (67.00%), severe bronchial asthma (33.00%). There was a significant association between the length of the index finger and asthma severity (p < 0.05).Conclusion: There is a relationship between chi văn location and the severity of bronchial asthma: Phong quan is associated with mild asthma, Khi quan with both mild and severe asthma, and Menh quan with severe asthma.
Keywords: The index finger, severity of asthma, pediatric patients 3 years old and younger.